1994
DOI: 10.1002/jsfa.2740650109
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the insoluble residues produced by the Klason lignin and acid detergent lignin procedures

Abstract: Two methods-Klason lignin (KL) and acid detergent lignin ( A D L F for determining lignin concentration in plants were compared using stem material from lucerne (Medicago satioa L), cocksfoot (Dactylis glomerata L) and switchgrass (Panicurn virgatum L), at three stages of maturity, and leaf samples from lucerne and cocksfoot. For all forages, KL values were higher than ADL values. Lucerne samples, which had crude protein levels twice that of the grass species, had KL values that were only 30-40% higher than AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
203
0
24

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(250 citation statements)
references
References 18 publications
(7 reference statements)
19
203
0
24
Order By: Relevance
“…These values reinforce that protein correction is mandatory to accurately estimate KL contents in tropical forages. The pattern obtained here agrees with previous assessment of protein contamination on KL in tropical forages (Gomes et al, 2011), but disagrees with Hatfield et al (1994), who found that CP content in samples is not correlated with the degree of protein contamination in lignin residues. At least part of the greater protein contamination in legumes can be traced back to the greater tannin content of this group, which favors the formation of insoluble complexes with the protein components of forages (Van Soest, 1994 Considering that protein contamination is relevant for KL estimates, a procedure for protein correction must be recommended to correctly obtain lignin content and to estimate more reliable relationships between rate and extent of cell degradation in the rumen.…”
Section: Contaminação Proteica Sobre Os Teores De Lignina Klason Em Gsupporting
confidence: 72%
“…These values reinforce that protein correction is mandatory to accurately estimate KL contents in tropical forages. The pattern obtained here agrees with previous assessment of protein contamination on KL in tropical forages (Gomes et al, 2011), but disagrees with Hatfield et al (1994), who found that CP content in samples is not correlated with the degree of protein contamination in lignin residues. At least part of the greater protein contamination in legumes can be traced back to the greater tannin content of this group, which favors the formation of insoluble complexes with the protein components of forages (Van Soest, 1994 Considering that protein contamination is relevant for KL estimates, a procedure for protein correction must be recommended to correctly obtain lignin content and to estimate more reliable relationships between rate and extent of cell degradation in the rumen.…”
Section: Contaminação Proteica Sobre Os Teores De Lignina Klason Em Gsupporting
confidence: 72%
“…The brown residue remaining after two-stage corn stover hydrolysis likely includes lignin, insoluble polysaccharides, any insoluble hydrolysis byproducts, protein, and ash. We have not yet characterized the lignin byproduct, but it is likely to resemble lignin produced by other acid hydrolysis processes, e.g., Klason lignin (43,52).…”
Section: Resultsmentioning
confidence: 99%
“…Para a determinação da lignina, adotou-se o mé-todo descrito por THEANDER e WESTERLUND (1986) e HATFIELD et al (1994), por intermédio do qual amostras de 100 mg (1 mm) foram submetidas à pré-hidrólise, durante uma hora, à temperatura ambiente, com a adição de 1,5 mL de ácido sulfúrico 72% (12M). Em seguida, a solução foi diluída para 0,4 M com a adição de 43,5 mL de água destilada, quando a amostra foi submetida à nova hidrólise (1 hora, 120 ±1 o C), na mesma autoclave já descrita e utilizada para a determinação de FDN.…”
Section: Análises Químicasunclassified